KORELASI LAMA MENDERITA DIABETES MELLITUS DAN TINGKAT PERAWATAN DIRI PENDERITA DIABETES MELLITUS TIPE 2 - Khoiriyah, Siti; Noorma, Nilam; Hartati, Sri; Santoso, Raden Bagus Edy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Diabetes Mellitus (DM) is a chronic metabolic disease characterized by increased blood glucose levels as a result of impaired insulin secretion, insulin resistance. Based on data from the Padangsidimpuan City Health Office, there were 885 cases in 2020, an increase to 921 cases in 2021, and a sharp jump to 2,276 cases in 2022. The purpose of the study was to determine the correlation between the duration of diabetes mellitus and the level of self-care of patients with type 2 diabetes mellitus. The research design used in this study was cross sectional. The research was conducted at the Sidangkal Health Center work area in July 2023. The population was 226 people with diabetes mellitus at Sidangkal Health Center. The sample amounted to 145 respondents. The sampling technique used in this study was non probability sampling with purposive sampling method. Data analysis was done univariate and bivariate. The results showed a relationship between the length of time suffering from DM (p value: 0.04). It is recommended that respondents can increase efforts to obtain useful information and insights to improve self-care for patients with type 2 diabetes mellitus.Keywords: Diabetes, length of stay, level of self-care